Spontaneous Control of HIV Replication, but not HAART-Induced Viral Suppression, Is Associated With Lower Activation of Immune Cell (2014)
ABSTRACT: HIV replication control is important to reduce AIDS progression. We determined frequency and activation status of immune cells in spontaneous HIV controllers vs. individuals with highly active antiretroviral therapy (HAART)-controlled viral load. HIV controllers exhibited significantly higher frequency of CD4+ T cells and myeloid dendritic cells compared with HAART-controlled viral load. Addition ally, HIV controllers have a significantly lower percentage of cells expressing activation markers on CD4+ and CD8+ T cells, myeloid dendritic cells, and natural killer cells. These findings suggest that during HIV infection, conservation of a normal frequency and physi ological range of immune activation is associated with spontaneous, but not HAART-induced, control of viral replication.